Consumption of non-prescription medications in nursing students - Chanchicocha Carrillo, Lucas Saúl; Lascano Sánchez, Adriana del Rocío (Enfermería Cuidándote, 2026)
Introduction: Self-medication, understood as the consumption of medications without medical supervision, is a prevalent practice among nursing students. Factors such as academic pressure, access to medications and the false security derived from their academic training contribute to this problem.Objective: To analyze the consumption of medications without a medical prescription in students in the fifth, sixth and seventh semesters of the Nursing Degree.Methodology: A descriptive, transversal and quantitative study was carried out with a sample of 168 students. A validated instrument was used to collect sociodemographic information and self-medication practices. The data were analyzed using frequencies and percentages.Results: 55.4% of students reported self-medication, mainly to treat mild symptoms such as body aches (19%) and colds (13.7%). The main reasons were saving time and money (39.9%). The most commonly used medications were acetaminophen (49.4%) and antibiotics (19.6%). The Internet was the main source of information (15.5%). Although 88.7% recognized the risks, 59.5% considered self-medication “moderately safe”.Conclusions: Self-medication is common among nursing students, driven by the perception of convenience and prior knowledge. It is necessary to reinforce their training in the rational use of medications to guarantee safe and responsible practices in their future professional work.
Keywords: Drug Utilization; Nursing Students; Over the Counter Drugs; Pharmacovigilance; Self Medication